Mapping Extreme Right Ideology - Bruter, M. author. aut Link
XIII, 236 p.
Keywords: An explanation of variations in the discourses and electoral success of 25 extreme right parties across 17 European political systems. The book shows how the European extreme right is mapped by the positions of parties and voters on two ideological dimensions, and how the match between these determines electoral success.